(untitled) (Revista de História da UEG (REVHIST), 2019)
Abstract: The town of São José de Taquari, nowadays Taquari, Rio Grande do Sul, was officially founded in the post-colonial period in 1760. At the beginning of the 19th century, Taquari grew demographically, until 1849 when it emancipated itself from Triunfo and then had political and administrative autonomy, with the category of village. In this context, the books of the City Council of Taquari are an important source of research to identify the subjects elected as Council members and to investigate the main structural emergencies of the municipality. This text is about the historical contextualization, settlement and economic development of Taquari. This situation was analyzed from the Book of Registration of Offices, Representations addressed to the Provincial, and General Government from 1850 to 1852, meeting the requests for urban and economic development of the municipality sent to the Presidency of the Province. Based on this research, it was possible to see the urbanization model of the end of the 19th century in the countryside of Rio Grande do Sul. Keywords: Regional history. Taquari/RS. City Council. Urbanization.